Profile of Rodenticide Poisoning at Vijayanagar Institute of Medical Sciences (VIMS), Ballari District, Karnataka, India: Retrospective Analysis of Cases from 2016 to 2020 - Gururaj Biradar; Charan Kishor Shetty; Pavanchand Shetty H; V Yogiraj (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Poisoning is the major health problem in developing countries like India. Rodenticides are thesubstances used to kill rats. Rodenticides are one of the commonest substances used for poisoning in Indiaone of the reasons is that it is easily available and cheaper than other pesticides They differ from chemicalcomposition and toxicity profile. Prognosis mainly depends on chemical content of poison.Methods: A retrospective descriptive 6 -year review of data from 597 rodenticide poisoning autopsiesperformed by the Department of Forensic Medicine at Vijayanagar Institute of Medical Sciences (VIMS),Ballari, Karnataka, India between January 1, 2015, and December 31, 2020, was carried out. Data wereobtained from judicial requisitions, autopsy reports, toxicology, and histology results. Different variables likethe gender, age-wise distribution of cases, marital status,profession,antemortem laboratory investigationsand manner of death were analysed. The data were analysed using Statistical Package for Social Sciences(SPSS) version 27.0.Results: Out of 597autopsy cases, majority of the cases 492 (82%) were male, 105 (18%) were female.Most common age group was 51 to 60 years 152 (45.23%) cases, followed by 41 to 50 years 140 (26.19%)cases. Most victims were married 469 (79%) and by profession were farmers 292 (48.91%) cases. Majorityof the cases were mostly reported in the night 454 (76.04%).Antemortem laboratory investigations data likeprothrombin time (PT), activated partial thromboplastin time (APTT), aspartate aminotransferase (AST),alanine aminotransferase (ALT), total bilirubin waselevated in majority of the cases. Manner of death wassuicidalin 497(83%) cases.Conclusions: Rodenticide poisoning is quite common and treatable, most of the time it is suicidal in nature.Public should be educated regarding consequences of poisoning. Family support and proper counselling forhigh-risk groups may decrease these incidences